Antioxidant Activity and Total Flavonoid Propolis Stingless Bee - Akhmad Endang Zainal Hasan; Ukhradiya Maharaniq Safira; Anita Purnamasari; Sri Wardatun (JURNAL AGROINDUSTRI HALAL, 2023)
Propolis from Indonesia contains secondary metabolites which include flavonoids and other organic compounds. The ethanol extract of 70% propolis Trigona spp from Pandeglang can be used as an antibacterial compound. The purpose of this study was to examine the toxicity of the propolis and nanopropolis with an LC50 value, test the antioxidant activity with an IC50 value, and determine the total flavonoid content. LC50 was determined by the BSLT method on Artemia salina Leach larvae. The antioxidant activity was tested using the DPPH method (1,1 diphenyl-2-picrylhydrazil), and the determination of flavonoid content was carried out with aluminum chloride. The results showed that the LC50 value of propolis was 16.010 ppm, and for 20% nanopropolis was 18.689 ppm. Antioxidant activity obtained IC50 value for propolis is 95.54593 ppm, for 20% nanopropolis is 527.7939 ppm. The total flavonoid content of the propolis was 2.1123%, and the total flavonoid content for the nanopropolis equivalent extract was 1.5293%.